Effects of water and CMA in mitigating industrial road dust resuspension. (April 2016) - Amato, Fulvio; Escrig, Alberto; Sanfelix, Vicenta; Celades, Irina; Reche, Cristina; Monfort, Eliseo; Querol, Xavier
Abstract: Water spraying and/or chemical suppressants such as salts and polymers have been suggested to reduce road dust resuspension due to their capability to increase adhesion, and therefore the effective size and weight of particles, but contrasting results have been obtained so further testing are needed. This study presents the first results of street washing and Calcium Magnesium Acetate (CMA) efficiencies at two industrial roads (paved and unpaved) in the Mediterranean region where the high solar radiation, warm climate, and scarce precipitation, may play a key role in determining the efficiency of mitigation techniques Results show that, at both sites, street washing (water only) was more effective than CMA. Street washing made observe 18% (daily basis) and >90% (first hour) reductions of kerbside PM10 concentrations for the paved and unpaved road respectively, while with CMA PM10 decrease was generally lower and with less statistical significance. Highlights: First results of mitigation tests for industrial dust resuspension in Southern Europe are presented. Paved and unpaved road were studied. Water flushing revealed higher efficiency than CaMg Acetate at paved and unpaved roads.